2012
DOI: 10.1016/j.jhep.2012.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Is blood of uncomplicated hemochromatosis patients safe and effective for blood transfusion? A systematic review

Abstract: Hemochromatosis is a disorder of the iron metabolism, characterized by high body iron content, necessitating frequent phlebotomies to remove excess iron. In some countries, this blood is discarded and not used for blood transfusion because of the non-voluntary character of this donation, and because a potential risk of microbial contamination of the donor blood is assumed. A systematic review was performed in order to collect and critically examine solid evidence with regard to the effectiveness and safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
26
0
2
Order By: Relevance
“…In a systematic review of the literature on haemochromatosis and blood donation, De Buck et al . came to the conclusion that blood products should be released for transfusion once iron levels are normalized. Our approach is to clear blood when the ferritin level falls below 300 ng/ml, future research on which we can safely base our practice is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of the literature on haemochromatosis and blood donation, De Buck et al . came to the conclusion that blood products should be released for transfusion once iron levels are normalized. Our approach is to clear blood when the ferritin level falls below 300 ng/ml, future research on which we can safely base our practice is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the absence of definite in vivo data excluding an association between HH and a higher risk of bacterial and viral contamination of derived blood, ruling out hyperferritinemia might increase blood transfusion safety. In a systematic review of the literature on haemochromatosis and blood donation, De Buck et al [25] came to the conclusion that blood products should be released for transfusion once iron levels are normalized. Our approach is to clear blood when the ferritin level falls below 300 ng/ml, future research on which we can safely base our practice is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A web‐based questionnaire revealed that in 24 of 33 countries, individuals with a genetic susceptibility to hemochromatosis are accepted as blood donors, with some of them accepting asymptomatic or even symptomatic patients as blood donor . In other countries, individuals with a genetic susceptibility are entirely excluded although the few available (low quality) studies suggest that blood products from donors with hemochromatosis without iron overload can safely be used in patients . In addition, in male‐to‐male sex policies, there is a lack of hard evidence supporting a certain deferral policy , which explains the heterogeneity in deferral policies among countries.…”
Section: Donor Selection Criteriamentioning
confidence: 99%
“…Also, harmonization of the blood donor selection policy among countries allowing hemochromatosis patients to donate blood once iron levels are normalized is needed. 18 In 2015, a systematic review was performed to investigate whether to investigate whether male blood donors, having sex with men, present a risk of TTIs in Western countries. Fifteen low-quality observational studies suggested a link between blood donors who were MSM and HIV-1 infection, but the evidence is too limited to recommend a precise deferral period.…”
Section: Systematic Reviewsmentioning
confidence: 99%